THE TECHNOLOGY OF USING EDUCATIONAL PROJECTS AND DIDACTIC TOOLS IN THE DEVELOPMENT OF COGNITIVE ACTIVITY OF FUTURE TEACHERS BASED ON AN INNOVATIVE APPROACH (Intent Research Scientific Journal, 2023)
In this arncle information is given on projects for the development of knowledge activity of future pedagogical personnel based on an innovative approach, the use of didactic tools, active methods of foreign scientists, and modernforms of active teaching This article can be used by students, masters, primary school teachers, researchers.